2022
DOI: 10.1108/ecam-08-2021-0731
|View full text |Cite
|
Sign up to set email alerts
|

Complex network-based research on organization collaboration and cooperation governance responding to COVID-19

Abstract: PurposeWith multiple-related organizations, worldwide infections, deep economic recession and public disorder, and large consumption amount of anti-epidemic resources, the coronavirus disease 2019 (COVID-19) has been defined as a public health emergency of international concern (PHEIC). Nowadays, Wuhan has recovered from the pandemic disaster and reentered normalization. The purposes of this study are to (1) summarize organization collaboration patterns, successful experience and latent defects under across-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…This discovery further applies the notion of public leadership to collaborative investigations within the field of public management. Nevertheless, organizational outcomes and empirical findings regarding collaborative administration are not entirely consistent, according to a recent systematic review [ 144 ]. The identification of a substantial connotation between PHD and collaborative administration in this study strengthens the validity of the prior empirical findings.…”
Section: Discussionmentioning
confidence: 99%
“…This discovery further applies the notion of public leadership to collaborative investigations within the field of public management. Nevertheless, organizational outcomes and empirical findings regarding collaborative administration are not entirely consistent, according to a recent systematic review [ 144 ]. The identification of a substantial connotation between PHD and collaborative administration in this study strengthens the validity of the prior empirical findings.…”
Section: Discussionmentioning
confidence: 99%
“…C1 depicts the difficulty of being physically present on the operation site to collaborate and seek information on the quality of cross-border projects. The collaboration process in QA has been impeded by the pandemic mitigation measures and the fear of getting infected (Oo et al, 2021;Rankohi et al, 2022;Yang et al, 2023). However, this stimulates organisations to devise innovative ways to collaborate and communicate with experts and workers and supervise and inspect works/services from remote locations.…”
Section: Interrelationships Between the Critical Challengesmentioning
confidence: 99%
“…After COVID-19, future prospect of fast-track projects was greatly realized by the construction industry stakeholders specially on medical care related projects (Gara et al, 2022). Telephonic conversations with construction industry practitioners in the US revealed that new opportunities for fast-track application emerged through construction of medical facilities on accelerated schedule and emergency basis during COVID-19 (Yang et al, 2022). Decreasing the project timeline is one of the main goals of every project manager (Feylizadeh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%